UJI EFEKTIVITAS EKSTRAK ETANOL DAUN RARU (Cotylelobium Melanoxylon) SEBAGAI ANTIINFLAMASI TERHADAP EDEMA KAKI TIKUS YANG DI INDUKSI KARAGENAN TAHUN 2023 - Marbun, Novarianti (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2025)
Flavonoids contained in raru leaves (Cotylelobium Melanoxylon) have anti- inflammatory activity. This study aims to determine the anti-inflammatory effect of raru leaf extract (Cotylelobium Melanoxylon) on white rats. Tests were carried out by producing edema on rat feet induced by 1% carrageenan. The anti- inflammatory effect test was divided into 5 treatment groups, each treatment group consisted of 3 rats, group 1 (negative control) was given CMC 0.5% Na suspension, group 2 (positive control) was given 2.25 mg/day diclofenac Na suspension. kgBB, group 3 raru leaf extract suspension dose of 50 mg/kgBB, group 4 raru leaf extract dose 100 mg/kgBB, and raru leaf extract dose of 150 mg/kgBB. The extract used the percolation method, with 70% ethanol solvent, measurement of inflammation volume was measured using a pletistometer, carried out for 180 minutes with an interval of 30 minutes after being induced with 1% carrageenan. From the results of this study, high doses of raru leaf extract have an anti-inflammatory effect. Data were analyzed using one way ANOVA. the data of this study that a dose of 150 mg/kgBB, is the dose with the most effect which is almost equivalent to the positive control group as an anti- inflammatory.